Study on test dynamics method of non-full loading firing for multiple launch rocket system. (1st May 2019) - Miao, Yunfei; Wang, Guoping; Rui, Xiaoting; Tu, Tianxiong
Highlights: The dynamics model and topology of Multiple Launch Rocket System(MLRS) is established using the transfer matrix method for multibody systems. The vibration characteristics and dynamics response of MLRS is simulated, and the relevant modal test are conducted to validate the correctness of simulation. The launch and flight dynamic simulation system for MLRS is developed, and the genetic algorithm is introduced to optimize the launch modes of rockets. In order to optimize the launch modes of rockets, the genetic algorithm is introduced. The relevant firing test are conducted to validate the correctness of the simulated results. Abstract: This paper studies the test dynamics method of non-full loading firing for multiple launch rocket system (MLRS), and provides a new method for dynamics analysis of the MLRS coupled with rigid bodies and elastic bodies. The launch dynamics model, eigenfrequency equations and dynamics response equations of the MLRS are established using the launch dynamics and transfer matrix method for multibody systems (MSTMM). The corresponding vibration characteristics and dynamics response are simulated, and the simulated results are verified by a series of tests directly, including modal test, pulse thrust test. Then, the simulation system of launch and flight dynamics of the MLRS is developed combining the Monte Carlo simulation technology. The initial disturbance and firing precision are simulated and verified by the live firing test. On above basis, the relationship between the dynamics characteristics and firing precision of the MLRS is analyzed. And then, the test dynamics method of non-full loading firing is proposed for reducing the rocket consumption in firing precision test by optimizing the launch modes of the MLRS. Finally, a seven-shot non-full loading firing test scheme for a practical MLRS is designed. And the correctness of the scheme is proved by practical contrastive firing test. The test results show that the amount of the rockets consumption in firing precision test is reduced by 61% compared with the conventional test method.